The princess and the moon - Ikeda, Daisaku; Wildsmith, Brian (New York : Knopf, 1992)
Sophie, a bad-tempered and unhappy child, changes her view of the world when the Great Moon Rabbit carries her to the moon and shows her how pleasant and happy people can be.
Translation of: Otsukisama to ojo.
Booklist
School Library Journal
Horn Book Magazine
4.8
K-3
Keywords: Behavior -- Fiction; Rabbits -- Fiction; Rabbits -- Fiction; Moon -- Fiction; Moon -- Fiction